2022
DOI: 10.1177/09596518221102204
|View full text |Cite
|
Sign up to set email alerts
|

Robust stabilization for an autonomous underwater vehicle motion based on descriptor time-delay model

Abstract: This article introduces a new technique for stabilizing autonomous underwater vehicles in the descriptor model. Autonomous underwater vehicle stabilization is limited by several constraints, including time-variable uncertainty, time delay, and disturbances. The interaction of descriptor system requirements and the issues mentioned above adds complexities. This study outlines the delay-dependent [Formula: see text] robust stability achieved through memory-less and memory state feedback. Furthermore, a less cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…From equation (13), it is clearly observed that _ V 1 ł 0 since k x , k y , k z . 0; hence, the proposed kinematic controller is stable.…”
Section: Kinematic Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…From equation (13), it is clearly observed that _ V 1 ł 0 since k x , k y , k z . 0; hence, the proposed kinematic controller is stable.…”
Section: Kinematic Controllermentioning
confidence: 99%
“…In the literature, different control methods have been suggested to control the motion of underwater vehicles. The recent advanced control approaches like backstepping control, 5 fuzzy control, 6 time delay control (TDC), 7 neural network control, 8 sliding mode control (SMC), 911 higher-order sliding mode control (HSMC), 12 H control, 13 model predictive control (MPC), 14 adaptive control, 15 and the combination of these control approaches are utilized to enhance the tracking efficiency of these vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…A descriptor time-delay AUV model has been considered for the design of a robust H control system. 19 The authors have developed robust sliding mode and adaptive sliding mode control systems for AUVs. 2022 Model predictive control (MPC) systems were also designed for AUVs under practical constraints.…”
Section: Introductionmentioning
confidence: 99%